PENINGKATAN PEMBELAJARAN ESTAFET MELALUI METODE BERMAIN PEMBELAJARAN PENJASKES - Yudo Prastowo; Kaswari Kaswari; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract:research aims to understand the influence of a method of play of the results of the learning relay races on school tuition smpn 05 singkawang .A method that is used is research methodology the act of class .The subject of research in this study took the whole grade students viiif smpn 05 singkawang a total of 21 students .Data analysis was done using a descriptive analysis. The research results obtained the value of planning learning run relay using (APKG) 1 with the results of the average value of 3.75 in kreteria good, the value of learning implementation run relay using (APKG) 2 with the results of the average value of 3.90 in kreteria good, average yield learning run relay on grade VIIIF SMP 05 Singkawang has increased between cycles. For the average prasiklus value 64.02, cycle 1 average 71.82 and cycle 2 the average value of 107.5. Overall the results of the research that has been done with regard to the improvement of the learning atletic. material run relay based on the results obtained by ketuntasan students, namely as a whole is 66.66% amounted to 14 students with criteria are. Key words: Method Play , Increased Learning Relay Races